Impacts of human activity on reindeer and caribou: The matter - Vistnes, Ingunn; Nellemann, Christian (Rangifer, 2007)
The impacts of human activity and infrastructure development on reindeer and caribou (Rangifer tarandus) have been studied for decades and have resulted in numerous debates among scientists, developers and indigenous people affected. Herein, we discuss the development within this field of research in the context of choice of spatial and temporal scale and concurrent trends in wildlife disturbance studies. Before the 1980s, the vast majority of Rangifer disturbance studies were behavioural studies of individual animals exposed directly to potential disturbance sources. Most of these local studies reported few and short-term impacts on Rangifer. Around the mid 1980s focus shifted to regional scale landscape ecology studies, reporting that reindeer and caribou reduced the use of areas within 5 km from infrastructure and human activity by 50-95%, depending on type of disturbance, landscape, season, sensitivity of herds, and sex and age distribution of animals. In most cases where avoidance was documented a smaller fraction of the animals, typically bulls, were still observed closer to infrastructure or human activity. Local-scale behavioural studies of individual animals may provide complementary information, but will alone seriously underestimate potential regional impacts. Of 85 studies reviewed, 83% of the regional studies concluded that the impacts of human activity were significant, while only 13% of the local studies did the same. Traditional ecological knowledge may further increase our understanding of disturbance effects.Effekter av menneskelig aktivitet på rein og caribou: Betydningen av valg av skalaAbstract in Norwegian / Sammendrag: Effektene av menneskelig aktivitet og utbygging på rein og caribou (Rangifer tarandus) har vært studert i flere tiår og har resultert i utallige debatter mellom forskere, utbyggere og berørt urbefolkning. I denne artikkelen diskuterer vi utviklingen innenfor dette forskningsfeltet i forhold til valg av skala i tid og rom, og i forhold til trender innen forskning på ...